QR Code and Face Recognition-Based Vehicle Key Validation System in SIPAKAD Application: Telekomunikasi Militer - Adi Setiawan; Vincensius Arga Yoda; Yudhi Darmawan (Jurnal Telkommil, 2026)
Vehicle management in the military, particularly the Army, requires a secure, fast, and efficient system to support daily operations. Manual processes for driver identity verification and vehicle access have proven to be ineffective and prone to errors. This study aims to design and implement a vehicle key pickup and return validation system based on QR Code technology and face recognition through a mobile application named SIPAKAD, which is a Progressive Web App (PWA). This system was developed to enhance security, efficiency, and transparency in the management of government vehicles, particularly within the military institution of Poltekad. QR Code technology is used to identify vehicles, while face recognition serves as biometric authentication for drivers before accessing vehicle keys. The system is built using PHP, MySQL, Flask (Python), and integrated with Firebase Cloud Messaging for real-time notifications. It also uses the Flask framework as the backend and the MQTT protocol for communication between IoT (Internet of Things) devices. Testing conducted with Raspberry Pi 3B showed that the highest validation accuracy was achieved in straight face conditions with bright lighting, with an average total accuracy of 43.99% across all four conditions, while the average total response time was 5.2 seconds. The implementation results show that this system is capable of reducing identification time, thereby accelerating the validation process, minimizing manual errors, and supporting more modern and documented vehicle data management. This research makes a significant contribution to supporting digital transformation and operational security of military vehicles within military institutions.